2022
DOI: 10.1038/s41598-022-13912-9
|View full text |Cite
|
Sign up to set email alerts
|

Heart age estimated using explainable advanced electrocardiography

Abstract: Electrocardiographic (ECG) Heart Age conveying cardiovascular risk has been estimated by both Bayesian and artificial intelligence approaches. We hypothesised that explainable measures from the 10-s 12-lead ECG could successfully predict Bayesian 5-min ECG Heart Age. Advanced analysis was performed on ECGs from healthy subjects and patients with cardiovascular risk or proven heart disease. Regression models were used to predict patients’ Bayesian 5-min ECG Heart Ages from their standard, resting 10-s 12-lead E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…The study excluded patients with LVEF <55%. A-ECG scores previously validated for the detection of reduced LVEF were also applied to this cohort, confirming a low likelihood of left ventricular systolic dysfunction for both the control and diastolic dysfunction cohorts (7 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] % and 13 [4-33] %, respectively), where a probability of >50% was considered a high likelihood.…”
Section: Study Populationmentioning
confidence: 55%
See 1 more Smart Citation
“…The study excluded patients with LVEF <55%. A-ECG scores previously validated for the detection of reduced LVEF were also applied to this cohort, confirming a low likelihood of left ventricular systolic dysfunction for both the control and diastolic dysfunction cohorts (7 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] % and 13 [4-33] %, respectively), where a probability of >50% was considered a high likelihood.…”
Section: Study Populationmentioning
confidence: 55%
“…A-ECG analysis on standard 10-sec ECGs enables improved diagnostic performance by incorporating not only conventional ECG measurements such as waveform amplitudes, axes and durations, but also measures of derived three-dimensional vectorcardiography (VCG) and waveform complexity via singular value decomposition. [10][11][12] . A-ECG has been able to discriminate between health and disease in several conditions such as coronary artery disease, cardiomyopathy, LV hypertrophy and LV systolic dysfunction, with notably higher diagnostic accuracy compared to conventional ECG 10,13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that ECG analyses utilizing deep learning approaches to AI-based ECG may predict mortality, cardiac arrhythmias, cardiac function, heart failure, valvular heart disease, and electrolyte abnormalities ( 7 12 , 35 , 36 ). By comparing the ECG age calculated via deep neural networks to the CA, new information on mortality and CVD risk factors has recently been derived ( 8 , 13 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many risk factors for CVD could be reduced by lifestyle modifications such as quitting smoking, changing one's diet, and increasing one's physical activity. The format of the heart age presentation could help patients understand and motivate them regarding their CVD risk ( 35 ). Patients changing their lifestyles can contribute to patient-centered care that positively affects the outcome of long-term CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Resting 12-lead ECG data for each subject was collected from the local ECG storage system (MUSE® Cardiology Information System, Version 8.0 SP2, GE Healthcare, IL, USA) and exported into anonymized xml files with coded identification. The xml files were analyzed digitally using previously described semi-automated software developed in-house 8 , 12 . The following ECG measures were included into the ECG prognosis score analysis: conventional ECG parameters including scalar durations, axes, and amplitudes; vectorcardiographic measures derived using Kors’ transform 13 including spatial durations, axes, and amplitudes; and QRS-wave and T-wave complexity measures quantified using singular value decomposition 8 .…”
Section: Methodsmentioning
confidence: 99%